F Forecasting Broiler Sales on CV. Berkah Bersama: Forecasting Broiler Sales on CV. Berkah Bersama - Muta Ali, Abdul; Ismaiyah, Ismaiyah (UMBanjarmasin, 2021)
The purpose of this study was to find out forecasting broiler chicken sales at CV. Berkah Bersama with using the trend moment method in May to July 2021. Previously the method was tested by its accuracy using the Mean Absolute Percentage Error (MAPE) calculation method. The data used in the form of sales data in the perioe January to April 2021. The result of the calculation of the accuracy of the trend moment method are 3% which indicate that the method is feasibleor can be used to predict the sale of broiler chicken on CV. Berkah Bersama. The result of calculation of forecasting chicken sales in the period May, June and July are equal to 60,957.90 Kg, 62,739.79 Kg dan 64,521.68 Kg. Keywords : Sales forecasting, Trend Moment Method, MAPE